2019
DOI: 10.1186/s13287-019-1162-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stem cell therapy for pulmonary arterial hypertension: a systematic review and meta-analysis of preclinical studies

Abstract: Background Despite significant progress in drug treatment, the prognosis of patients with advanced pulmonary arterial hypertension (PAH) remains extremely poor. Many preclinical studies have reported the efficacy of stem cell (SC) therapy for PAH; however, this approach remains controversial. The aim of this systematic review and meta-analysis is to assess the potential efficacy of SC therapy for PAH. Methods The Medline, EMBASE, Cochrane Library, and Web of Science dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…While immunogenicity is unrelated to MSC therapy [43,44], other significant risks still exist. Previous meta-analyses have shown no direct relationship between MSC administration and acute poisoning, systemic failure, malignancy, or death [47][48][49]. Regarding the safety and effectiveness of MSCs in the treatment of sepsis, phase 1 clinical trials have been conducted [43,44], but MSCs have not yet been used for the clinical treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…While immunogenicity is unrelated to MSC therapy [43,44], other significant risks still exist. Previous meta-analyses have shown no direct relationship between MSC administration and acute poisoning, systemic failure, malignancy, or death [47][48][49]. Regarding the safety and effectiveness of MSCs in the treatment of sepsis, phase 1 clinical trials have been conducted [43,44], but MSCs have not yet been used for the clinical treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of results suggested that SC therapy significantly improves mPAP and RVSP in PAH animals, indicating that SC treatment for PAH has promising prospects, particularly induced pluripotent stem cells. Unfortunately, the detailed dose–effect of SCs and their efficacy for PAH requires further study to provide standardization for clinical trials [ 139 ]. Moreover, increasing research has implied that imbalance in the immune response also participates in the pathogenesis of PAH.…”
Section: Therapy For Pahmentioning
confidence: 99%
“…A systematic review of preclinical animal studies including 29 articles reported effectivity of stem cell therapy for pulmonary arterial hypertension. 12 One clinical report including 2 adult cases of PH receiving stem cell therapy also showed clinical improvement. Reduction of oxygen therapy and increased activity index in one patient were noted after stem cell therapy, while another patient had improved clinical or PH condition.…”
Section: Discussionmentioning
confidence: 98%